Rice cultivars ability to change nutrient solution pH in the presence of aluminum - Mendonça, Renilton Joaquim de; Cambraia, José; Oliva, Marco Antonio; Oliveira, Juraci Alves de (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate aluminum effect on the ability of two rice cultivars, Fernandes (tolerant) and Maravilha (sensitive), to change the pH of nutrient solutions with different NO3-/NH4+ ratios. After plant exposure to 0 mM and 1.5 mM Al for 15 days, the amount of exudated protons, elongation, dry matter yield and Al content of roots and leaves were determined. Elongation and dry matter yield of roots and leaves reduced in the presence of Al independently of NO3-/NH4+ ratio, and this reduction was intensified with increasing of NH4+ concentration. Aluminum contents increased in roots and leaves with increasing of NH4+ concentration in nutrient solution. An alkalization of the nutrient solution containing N exclusively in NO3- form was observed, but this alkalization decreased with Al treatment. In nutrient solutions containing NH4+, on the contrary, an acidification was observed, which intensified with the increase of NH4+ concentration. The tolerant cultivar always consumed more protons of the nutrient solution containing N exclusively in the NO3- form and less protons of that containing NH4+, independently of the NO3-/NH4+ ratio. This cultivar, therefore, showed higher ability to adjust its protons balance, changing the pH to values that favored lower Al uptake and higher tolerance to aluminum.